Serum lactate in refractory out-of-hospital cardiac arrest: Post-hoc analysis of the Prague OHCA study - Dusik, Milan; Rob, Daniel; Smalcova, Jana; Havranek, Stepan; Karasek, Jiri; Smid, Ondrej; Brodska, Helena Lahoda; Kavalkova, Petra; Huptych, Michal; Bakker, Jan; Belohlavek, Jan (Resuscitation, 2023)
BACKGROUND: The severity of tissue hypoxia is routinely assessed by serum lactate. We aimed to determine whether early lactate levels predict outcomes in refractory out-of-hospital cardiac arrest (OHCA) treated by conventional and extracorporeal cardiopulmonary resuscitation (ECPR). METHODS: This study is a post-hoc analysis of a randomized Prague OHCA study (NCT01511666) assessing serum lactate levels in refractory OHCA treated by ECPR (the ECPR group) or conventional resuscitation with prehospital achieved return of spontaneous circulation (the ROSC group). Lactate concentrations measured on admission and every 4 hours (h) during the first 24 h were used to determine their relationship with the neurological outcome (the best Cerebral Performance Category score within 180 days post-cardiac arrest). RESULTS: In the ECPR group (92 patients, median age 58.5 years, 83% male) 26% attained a favorable neurological outcome. In the ROSC group (82 patients, median age 55 years, 83% male) 59% achieved a favorable neurological outcome. In ECPR patients lactate concentrations could discriminate favorable outcome patients, but not consistently in the ROSC group. On admission, serum lactate >14.0 mmol/L for ECPR (specificity 87.5%, sensitivity 54.4%) and >10.8 mmol/L for the ROSC group (specificity 83%, sensitivity 41.2%) predicted an unfavorable outcome. CONCLUSION: In refractory OHCA serum lactate concentrations measured anytime during the first 24 h after admission to the hospital were found to correlate with the outcome in patients treated by ECPR but not in patients with prehospital ROSC. A single lactate measurement is not enough for a reliable outcome prediction and cannot be used alone to guide treatment.
Keywords: Extracorporeal Membrane Oxygenation; Prognosis; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Hypoxia; Out-of-Hospital Cardiac Arrest; hypoxie; prognóza; mimotělní membránová oxygenace; mužské pohlaví; kardiopulmonální resuscitace; zástava srdce mimo nemocnici; ženské pohlaví; Cardiopulmonary Resuscitation; lidé; Male; Retrospective Studies; Female